A Time-gated Contactless Interrogation System for Frequency and Quality Factor Tracking in QCR to Investigate on Liquid Solution Microdroplets. (2016) - Ferrari, Marco; Baù, Marco; Masud, Mehedi; Ferrari, Vittorio
Abstract: In this work, a contactless interrogation via electromagnetic coupling based on time-gated techniques has been proposed for Quartz Crystal Resonator (QCR) to investigate on liquid solution microdroplets. The sensing of the resonator response is innovatively based on a heterodyne demodulation and autocorrelation analysis, providing high performances yet avoiding the use of expensive instruments and allowing to estimate both the sensor damped resonant frequency and the quality factor Q. The system works with interrogation distances up to few centimeters and has been experimentally validated by loading the QCR with microdroplets of different liquid microsamples.